Evaluasi Program Penanggulangan TBC Di Daerah Istimewa Yogyakarta (Studi pada Dinas Kesehatan DIY) - Siti Dwiana Atmawati; Winda Cindy Wulandari (Pascasarjana Universitas Jember, 2022)
Tuberculosis control in Indonesia has made a lot of progress, but nationally the Special Region of Yogyakarta (DIY) until the second quarter of 2022, Treatment Coverage ranks 13th, which is 24.6% (SITB, 2022). It is estimated that 9,000 TB cases must be found and treated. This study aims to evaluate the implementation of the TB control program in DIY. Assessment is carried out on process and output aspects in DIY mid-2022. This observational research was conducted at the DIY Health Office. The analysis was carried out descriptively on the process and output variables by comparing the results with the targets or standards set by the Ministry of Health. The 3 main indicators of TB elimination in DIY have not achieved the target, but the activities for the Prevention and Control of Tuberculosis (P2TB) in DIY have been going quite well.